Peningkatan Kompetensi Pedagogik Guru Melalui Pelatihan Menjadi Guru Inspiratif Dan Menyenangkan Untuk Guru-Guru Di Desa Kampar - Ramadhan, Syahri; Seprya, Roby; Rahayu, Evi; Guswanti, Nelia; Maghfiroh, Shofia (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2025)
The training to be an inspirational and fun teacher for teachers in Kampar Village is behind many problems in schools that show the fullness of teaching and learning that occurs to teachers and students. The service is carried out using methods with planning, implementation, post-activity, and practice methods, Q&A and discussion, and Evaluation and Feedback stages. This service is intended for elementary, middle, and high school teachers in Kampar Village as many as 20 teachers. The results of this training activity show that there is a change in the knowledge of teachers with competencies that a teacher must have, which includes hard skills and soft skills. Judging from the comparison of the results of Preetest and Posttest, there is a change in teachers' knowledge about being inspiring and fun teachers. So that teachers are moved to evaluate themselves and improve their ability to become inspirational and fun teachers. Given that these activities such as training are essential to support teachers' duties in teaching, it is hoped that in the future there will be similar activities that will continue to be carried out periodically and continuously by parties involved in education management, such as the government and institutions or the Education Management Foundation